ASSESSMENT OF THE RELATIONSHIP BETWEEN SERUM TWEAK LEVELS AND THE DEGREE OF VASCULAR INVOLVEMENT IN PATIENTS WITH STABLE ANGINA PECTORIS - Sirikci Vehbi; Findikli Huseyin Avni; Ozturk Savas (Sanamed)
Introduction: This study investigates the relationship between serum TWEAK levels and the degree of vascular involvement in patients with stable angina pectoris, offering insights beyond conventional cardiovascular risk factors.